(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article analyzes the microscopic mechanisms determining the physical nature of ferroelectric materials and thermodynamic models of phase transitions. The significance of thin-film structures based on hafnium oxide (HfO_2) in modern industry, specifically in microelectronics, is highlighted. The study provides a scientific basis for the prospects of utilizing the negative capacitance effect and ferroelectric tunnel junctions in neuromorphic computing systems.